The transcription factor Cabut coordinates energy metabolism and the circadian clock in response to sugar sensing. (27th April 2015) - Bartok, Osnat; Teesalu, Mari; Ashwall‐Fluss, Reut; Pandey, Varun; Hanan, Mor; Rovenko, Bohdana M; Poukkula, Minna; Havula, Essi; Moussaieff, Arieh; Vodala, Sadanand; Nahmias, Yaakov; Kadener, Sebastian; et al.
Abstract Nutrient sensing pathways adjust metabolism and physiological functions in response to food intake. For example, sugar feeding promotes lipogenesis by activating glycolytic and lipogenic genes through the Mondo/ChREBP‐Mlx transcription factor complex. Concomitantly, other metabolic routes are inhibited, but the mechanisms of transcriptional repression upon sugar sensing have remained elusive. Here, we characterize cabut (cbt), a transcription factor responsible for the repressive branch of the sugar sensing transcriptional network in Drosophila. We demonstrate that cbt is rapidly induced upon sugar feeding through direct regulation by Mondo‐Mlx. We found that CBT represses several metabolic targets in response to sugar feeding, including both isoforms of phosphoenolpyruvate carboxykinase (pepck). Deregulation of pepck1 (CG17725) in mlx mutants underlies imbalance of glycerol and glucose metabolism as well as developmental lethality. Furthermore, we demonstrate that cbt provides a regulatory link between nutrient sensing and the circadian clock. Specifically, we show that a subset of genes regulated by the circadian clock are also targets of CBT. Moreover, perturbation of CBT levels leads to deregulation of the circadian transcriptome and circadian behavioral patterns.